Rapid Analysis of Stable-HbA1c by High-Performance Liquid Chromatography - Kawasaki, Riichi; Kitamura, Takashi; Kato, Yoshio; Tukada, Toshihiko; Doi, Keiko; Nakayama, Toshimasa; Kawakami, Keiko (Japanese Journal of Clinical Chemistry, 1996)
We studied rapid analysis of stable-HbA1c (SA1c) by high-performance liquid chromatography (HPLC) on a non-porous cation-exchanger measuring 2.5μm in diameter, TSKgel Glyco-HSi. The HbA1c fraction separated on a conventional cation-exchanger, TSKgel Glyco-HS, was resolved into more than four fractions on TSKgel Glyco-HSi, and the main component of them was S-A1c and minors were labile-HbA1c (L-A1c) and unknown components. The S-A1c concentrations in blood obtained from a patient undergoing 100g oral glucose tolerance test (OGTT) were not altered over the course of the test (0 to 180 min), whereas L-A1c levels markedly increased in blood with higher glucose concentrations. The normal reference values obtained for S-A1c and L-A1c, were 4.0-4.6% and 1.5-2.4%, respectively. S-A1c could be analyzed in about 2 min by the fullautomated glycated hemoglobin analyzer, HLC-723GHb III (TOSOH). Coefficient of variation (C. V.) for the S-A1c value was less than 1.2%.